2006
DOI: 10.3998/ark.5550190.0007.218
|View full text |Cite
|
Sign up to set email alerts
|

A novel one pot Mannich synthesis of methylpiperidin phenols, methylphenylmorfolin phenols and methyltiophenylmorpholin phenols solvent-free and using infrared light irradiation

Abstract: A series of methylpiperidinyl phenols, methylphenylmorpholinyl phenols and methylthiophenylmorpholinyl phenols were synthesized in one-pot transformation by Mannich reactions using infrared irradiation under solvent-free conditions. The chemical structures of the compounds were proved by IR, 1 H NMR, 13 C NMR and MS spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…ACE inhibition has been proven to be effective in myocardial infarction, reducing complications, improving symptoms and attenuating the progression of cardiac insufficiency [8,10,11]. Additionally, ACE inhibitors attenuate not only the production of Ang II at a systemic and tissue level, but they also allow the accumulation of bradykinin because they inhibit its degradation [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACE inhibition has been proven to be effective in myocardial infarction, reducing complications, improving symptoms and attenuating the progression of cardiac insufficiency [8,10,11]. Additionally, ACE inhibitors attenuate not only the production of Ang II at a systemic and tissue level, but they also allow the accumulation of bradykinin because they inhibit its degradation [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TBTIF has a high affinity for ACE [10,33]. Furthermore, it is suggested that the increase in Ang(1-12) during this phase of infarction is to promote the production of components that counteract the damage caused to the heart, so that the production of Ang(1-7) and, as Ferrario et al [30] suggest, Ang(1-12) could be used as a quick-release substrate for the immediate production of the RAS components instead of being produced from angiotensinogen [8]. Burrell et al [34] showed that myocardial infarction generates an upregulation of mRNA of ACE and ACE2, as did we.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Stout's work, our group purposed to change the pyrrolidine ring and used the morpholine and thiomorpholine systems instead. In 2007 we synthetized and characterized a group of compounds derived from phenol, named LQM300 [32]. These new compounds were tested in rat model [33], from which the compounds ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The bis(alkylaminomethyl) hydroquinones 6a-6c were prepared by Mannich reactions, i.e., the reaction of 1,4-hydroquinone with paraformaldehyde and the corresponding secondary amine. 47,48 We have determined the structures of 4b, 4c, and 4d ( Fig. 1) and 5a and 5b (Fig.…”
Section: Synthesis and Characterization Of Hydroquinonesmentioning
confidence: 99%